Physiological aspect of apoptosis-regulating microRNAs expressions during fasting - Ulas, M.; Akbas, E.; Akbas, S.; Aktemur, G.; Durcanoglu, N.; Aksak, K.; Akalin, I. (Verduci Publisher, 2023)
OBJECTIVE: Fasting is an activi-ty that requires a certain calorie restriction with-out consuming food or drinks for a certain pe-riod of daytime. However, fasting triggers ma-ny complex events, including activating cellular stress response pathways, autophagy promo-tion, apoptosis pathways, and a change in hor-monal balance. Among the many events affect-ing the regulation of apoptosis, the expression of microRNAs (miRNAs) plays an important role. Therefore, we aimed to investigate the levels and importance of miRNA expression in fasting.PATIENTS AND METHODS: The expressions of 19 miRNAs regulating different pathways from saliva samples, isolated by matching healthy university students (n = 34) as group 1 (fasting for 17 consecutive hours) and group 2 (testing 70 minutes after meal consumption), were exam-ined using the real-time PCR method. RESULTS: In fasting, modulation of apoptotic pathways by miRNAs triggers anti-pathogenic ef-fects, and the adaptation of abnormal cells in the body decreases. For this reason, vital diseases, such as cancer, can be treated by preventing the proliferation and growth of cancerous cells by in-creasing programmed cell death due to the down -regulation expression mechanism of miRNAs.CONCLUSIONS: Our study aims to improve the knowledge about the mechanisms and func-tions of miRNAs in various apoptosis pathways during fasting and may be a model for further fu-ture physiological and pathological studies.
Keywords: Key MicroRNAs; Fasting; Polymerase chain reaction; Apoptotic pathways; MiR; 221-222